DEHYDRATION LEVELS AND DRINKING WATER CONSUMPTION ON WORK FATIGUE AT PT. PAL INDONESIA - Tri Ayu Rahma Lestari; Noeroel Widajati (Journal of Vocational Health Studies, 2025)
Background: Work fatigue among PT. PAL Indonesia workers occurs due to several factors, such as working under high temperatures and sunlight without the aid of temperature reducing equipment and the lack of easily accessible drinking water around the workplace, which can trigger dehydration in workers. Purpose: This study aims to analyze the strength of the relationship between drinking water consumption and dehydration on work fatigue in floating and digging dock workers at PT. PAL Indonesia. Method: This research is an observational study with a cross-sectional approach, involving a sample of 26 dock workers from the Harkan Division at PT. PAL Indonesia. Data collection was conducted through measuring work fatigue using a reaction timer, questionnaires, interviews, and observations. Result: The analysis between variables shows a strong relationship between dehydration and work fatigue of 0.606 and a very weak relationship between drinking water consumption and the incidence of work fatigue of 0.135. Conclusion: It is suggested that the company should regularly provide drinking water supplies for workers and place them in locations that are easily accessible. Apart from that, the company should encourage workers to consume more water instead of other drinks to protect them from possible diseases beyond work fatigue.